A search for the Standard Model Higgs boson via its decay to tau leptons and W bosons at the ATLAS detector - Boddy, C (2013)
Understanding the origin or Electroweak symmetry breaking within the Standard Model was a key motivation for the construction of the Large Hadron Collider (LHC) experiment at CERN. This thesis presents a search for evidence of Higgs boson production in the 4.7 fb−1 of collision data recorded at a centre-of-mass energy of 7 TeV at the ATLAS detector during 2011. This search is focused on signal events in which a Higgs boson is produced in the mass range 100 < mH < 180 GeV/c2 and subsequently decays to a pair of W bosons or a pair of tau leptons to final states with one hadronically decaying tau lepton and one light lepton. After an event selection criteria has been applied, the number of events in this data sample is consistent with the total background estimate and an upper limit is placed on the SM Higgs boson production rate at 95% confidence level. In addition, the prospects for measuring the SM Higgs coupling strength to tau leptons with the associated Higgs production channels and the full LHC dataset are also presented.